Intracellular pH of acid-tolerant ruminal bacteria. - Russell, J B (1991)
Acid-tolerant ruminal bacteria (Bacteroides ruminicola B1(4), Selenomonas ruminantium HD4, Streptococcus bovis JB1, Megasphaera elsdenii B159, and strain F) allowed their intracellular pH to decline as a function of extracellular pH and did not generate a large pH gradient across the cell membrane until the extracellular pH was low (less than 5.2). This decline in intracellular pH prevented an accumulation of volatile fatty acid anions inside the cells.